The management of human talent and the organizational behavior of the administratic workers of a public university in Lima-Peru - Acevedo, Jesus Enrique Reyes (Eximia, 2022)
The rapid changes occurring in business organizations makes it much neglected the elementary part of the internal movement of the company. That inner part is the human capital, part administrative, which moves all the organizational team management of human talent, and its impact on organizational behavior of the institutions, most institutions are trying to insert full steam in programs of change and innovation to accompany what happens in the atmosphere and around. This means changes in corporate culture and organizational behavior; and the management of human talent through habits and values and behaviors and attitudes of people are deeply affected, and the roles assumed by them and mutual relations. To change, to be the first to have a new organizational image, just it needs new patterns and evaluative study preparation. The management of human talent is deeper in the interior of each manager and their professional skills, consider their ways of understanding and understanding how important it is to consider vital elements to improve the organizational behavior of institutions seeking to maximize administrative potential through its administrative. Within the administrative labor framework, it is important teamwork, and be in constant training and modify their behavior patterns within the organization, which always asks, as administrative principle, and within our institution, often stops side, the relevant treatment, for not being properly prepared to take responsibility, they generate, and satisfied the same for each, as an administrative worker. The thesis is to obtain new forms of knowledge develop communication levels through management and management of human, or human talent, it helps to increase levels of behaving in the domestic society organization, leading to human disciplines and correlations between pairs and groups of administrative work. The thesis has studies on human talent management to improve organizational behavior, for which they influence and thus determine actions and valid recommendations for the implementation of the thesis within the population taken, even so, it is possible to improve constant as a fundamental element of contribution within the National University of Canete, in their administrative relations. The thesis develops ways as you can unify the individual with his behavior, considering some theoretical and methodological aspects of Human Resource Management, and how they create an effect on organizational behavior in administrative staff. That is is to systematize the application of human capital an ideal way to improve the admissions process, monitoring staff and working conditions within the National University of Canete.